ANALISIS RASIO LIKUIDITAS DAN SOLVABILITAS TERHADAP KINERJA PERUSAHAAN PADA PERBANKAN SYARIAH - purwanto, purwanto; Syahadatina, Rika (JURNAL AKUNTANSI DAN INVESTASI, 2018)
This study aims to analyze Islamic bank financial performance appraisal. One of them is by analyzing the profitability level of the relevant Islamic banks, which shows that Islamic banking gets the title of a healthy category of banks, analyzes Islamic banking financial performance using added value and financial ratios that show influence on banking financial performance sharia. The population in this study is a company in the period Islamic Sharia bank company which is listed on the Indonesian stock exchange with a total of 11 companies. The sample of this study was taken using a saturated sample technique that is by making the entire population as a sample. The analytical tool used in this study is a comparison with Indonesian tire regulations. Based on this research, it was concluded that there were 6 companies in good condition, namely indicator cash ratio below 3%. So it was concluded that there were 6 companies in good condition with DER indicator.